Perinatal outcomes among twin pregnancies with gestational diabetes mellitus: A nine-year retrospective cohort study - Lin, Dongxin; Fan, Dazhi; Li, Pengsheng; Chen, Gengdong; Rao, Jiaming; Zhou, Zixing; Zhang, Huishan; Luo, Xin; Ma, Huiting; Feng, Jingping; Lu, Demei; Wang, Lijuan; et al. (Frontiers in Public Health, 2022)
Objective To compare the outcomes between gestational diabetes mellitus (GDM) vs. non-GDM twin gestations. Methods A retrospective cohort study of 2,151 twin pregnancies was performed in a tertiary hospital in Foshan, China, 2012–2020. Pregnancy and neonatal outcomes were compared between women with vs. without GDM using 1:1 propensity score matching (PSM) and multivariable logistic models. For neonatal outcomes, generalized estimating equation (GEE) approach was used to address the intertwin correlation. Results Of the 2,151 participants, 472 women (21.9%) were diagnosed with GDM. Women with GDM were older and more likely to be overweight or obese, and more likely have chronic hypertension, assisted pregnancies and dichorionic twins. In the PSM cohort of 942 pregnancies, there was no statistical difference when comparing GDM twin pregnancies and non-GDM in any of the perinatal outcomes, especially in terms of preterm birth (PTB) <37 weeks (P = 0.715), large for gestational age (LGA) (P = 0.521) and neonatal respiratory distress (NRDS) (P = 0.206). In the entire cohort, no significant adjusted ORs for these outcomes were obtained from logistic regression models adjusted for confounders (aOR for PTB < 37 weeks: 1.25, 95% CI: 0.98–1.58; aOR for LGA: 1.26, 95% CI: 0.88–1.82; and aOR for NRDS, 1.05, 95% CI: 0.68–1.64). Conclusion Twin pregnancies with GDM and adequate prenatal care have comparable perinatal outcomes to those without.